Self-destructive behavior and information and communication technology - Santos, Ricardo Augusto dos (2023)
Objective: to identify productions on the relationship between self-injurious/suicidal behavior and Information and Communication Technology. Methods: this is a review that considered the period from 2016 to 2021, in the descriptors “comportamento autodestrutivo” (self-destructive behavior), “comportamento suicida” (suicidal behavior) and “Tecnologia de Informação” (Information Technology) and their translated versions in English and Spanish and, in the databases PsycInfo, IEEE Xplore, Science Direct and PubMed. Categorization of the surveyed productions was used. Results: from a first search of 262 articles, nine of them were analyzed. Three categories were constructed: Mental health and suicide; Internet/mobile application based intervention; Personalized attention to youth/adolescents. Most studies sought to understand the importance of using Information and Communication Technologies through mobile applications, which can be used both as a complement to face-to-face therapies and in the direct prevention of self-destructive behavior. Conclusion: Information and Communication Technologies are a suicide prevention strategy.